(untitled) (Revista Brasileira Multidisciplinar, 2025)
The work Torto Arado, designed by Itamar Vieira Júnior and published in 2018, is divided into three distinct parts. The first is reported from the perspective of the character Bibiana, the second by her sister Belonísia and the third by Santa Rita Pescadeira, a religious entity. The narrative employs a linear and fluid structure, with events that unfold predominantly chronologically, maintaining the reader’s involvement throughout the progression of the plot. Set in a fictional setting called Água Negra, the work evokes the classic vision of the northeastern backlands. The characters live on a farm in this environment, where several generations of families have taken root, perpetuating their traditions and cultures. Torto Arado offers a deep analysis of the multiple relationships between individuals and territories, as the characters attribute different meanings and symbols to them. Furthermore, the narrative allows for reflection on different forms of oppression, ensuring that history, memory and varied existential expressions are not erased by a single narrative. VIEIRA JÚNIOR, ITAMAR. Crooked plow. São Paulo: However, 2019.